The Implementation of the People's Business Credit (KUR) Program on the Welfare of Micro, Small, and Medium Enterprises (UMKM): A Study at BRI Bank, Lingkar Timur Unit Office, Bengkulu City, Indonesia - Purnawan, Heru; Suri, Evsa Wulan; Saputra, Noprian; Aprianty, Henny (JPSI (Journal of Public Sector Innovations), 2023)
One of the initiatives of the Indonesian government to encourage economic activities and business is the People's Business Credit (KUR) program. The purpose of this study is to analyze the implementation of the KUR program using Van Meter and Van Horn's policy implementation model, with variables including the scope and objectives of the policy, resource allocation, characteristics of implementing agents, disposition, and the surrounding environment. This study uses a qualitative method. Data collection is carried out through interviews, observation, and documentation (Sugiyono, 2010). Secondary data used in this study includes documentary studies or literature. The results of the study obtained: 1) The KUR procedure is guided by the Standard Operating Procedure (SOP) and Ministerial Regulation, which serve as guidelines for evaluating the eligibility of prospective borrowers. 2) The loan amount for Micro Enterprises in the KUR program is a maximum of IDR 25 million, while for Small and Medium Enterprises, it is a maximum of IDR 500 million. The majority of KUR providers are state- owned banks. 4) The KUR program is well received by the community, especially customers who need additional business capital. 5) KUR recipients are not on target because there are still many customers who have sufficient economic conditions, such as government officials, business actors, or civil servants. 6) The human resources implementing the KUR program are not permanent and often experience turnover due to work demands. 7) If a KUR customer dies, the program must be continued by his heirs. 8) The human resources implementing the KUR program in the field often do not provide a comprehensive understanding to customers regarding the provisions of the KUR contract, including risks, fines, requirements, and legal agreements.